Green supply chain management and green creativity: Implications for sustainability - Alabdily, Dhurgham Hassan; Marza, Ghaidaa Hamza; Abdulrasool, Ahmed Muhammadridha; Amanah, Ahmed Abdullah (International Journal of Management and Sustainability, 2025)
The purpose of this paper was to examine the beverage business in Iraq and the connections between green supply chain management, green creativity, barriers to green supply chain management, and sustainability in supply chain management. The objective was to investigate the interactions among these elements to affect the results of sustainability in this particular industrial sector in Iraq. The paper included 248 participants, all of whom were employees in Baghdad Soft Drinks Company, which is a private joint-stock company. Structured questionnaires based on validated scales were used to collect data. Data were analyzed using Stata structural equation modeling to examine direct and mediated effects between research variables (GSCM, GC, SSCM). The findings show that GSCM improves SSCM, and GC partially helps explain this link. BGCM is also useful in moderating the connection between GSCM and SSCM. Therefore, it is necessary to eliminate the barriers in order to maximize the impact of the environment on the Iraqi beverage industry. This article explores sustainability and how it would be used to improve the supply chain strategy using innovative approaches. It shows how Iraqi beverage companies, with the assistance of green methods, may overcome obstacles and guarantee a high degree of sustainability with long-term environmental, social, and economic impacts.